2005
DOI: 10.5433/1679-0367.2005v26n1p37
|View full text |Cite
|
Sign up to set email alerts
|

Capacidade funcional de idosos restritos ao domicílio, do conjunto Ruy Virmond Carnascialli, Londrina/PR

Abstract: ResumoA incapacidade funcional é definida pela presença de dificuldade no desempenho de atividades da vida cotidiana ou mesmo pela impossibilidade de desempenhá-las. O objetivo do estudo foi avaliar a incapacidade funcional de idosos restritos ao domicílio.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
11

Year Published

2010
2010
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 6 publications
1
2
0
11
Order By: Relevance
“…Feeding is a task of subsistence, which is performed almost automatically by the patients and preserved until the final phase of life. Results indicate that this was the most highly preserved function among the elderly, which agrees with a study developed in the United Kingdom that verified the order of restriction of activities, beginning with bathing, transferring, dressing, toileting and, finally, feeding (20) .…”
Section: Degree Of Dependencesupporting
confidence: 90%
“…Feeding is a task of subsistence, which is performed almost automatically by the patients and preserved until the final phase of life. Results indicate that this was the most highly preserved function among the elderly, which agrees with a study developed in the United Kingdom that verified the order of restriction of activities, beginning with bathing, transferring, dressing, toileting and, finally, feeding (20) .…”
Section: Degree Of Dependencesupporting
confidence: 90%
“…Maintaining and preserving the functional capacity of the elderly to perform the basic and instrumental activities of daily living are fundamental points for prolonging their independence for as long as possible and maintaining their functional capacity 13 . The present study found a high degree of incapacity in the elderly assessed (78% in the ADLs and 65.33% in the BADLs).…”
Section: Discussionmentioning
confidence: 99%
“…Outro aspecto que acreditamos vir a contribuir para a compreensão deste trabalho, que se baseia em dados, foram os resultados positivos em todos os casos que foram cuidados no domicílio pelas ações fisioterapêuticas implementadas a partir do Niefam com as famílias cadastradas, os quais fazem eco a estudos prévios (1)(2)(3)(4)(5).…”
Section: Considerações Finaisunclassified